Endothelial barrier protective properties of low molecular weight heparin: A novel potential tool in the prevention of cancer metastasis?. Issue 1 (20th June 2017) - Kevane, Barry; Egan, Karl; Allen, Seamus; Maguire, Patricia; Neary, Elaine; Lennon, Áine; Ní Áinle, Fionnuala
Abstract: Essentials Inhibition of tumor cell trans‐endothelial migration inhibits metastasis formation. Low molecular weight heparin (LMWH)‐mediated endothelial barrier protection was investigated. LMWH enhanced endothelial barrier activity and attenuated tumor cell transmigration. The cytoprotective activity of LMWH did not appear to be dependent on anticoagulant activity. Background: One of the key events in the progression of cancer metastasis is the trans‐endothelial migration of circulating tumor cells. Moreover, inhibition of tumor‐induced vascular permeability has been shown to inhibit metastasis in vivo. Low molecular weight heparin (LMWH) appears to confer a survival benefit in cancer but the underlying mechanisms are poorly understood. Objective: To characterise LMWH‐mediated endothelial barrier protection and to explore strategies to limit the LMWH‐associated haemorrhagic risk in this setting. Methods: Endothelial barrier function was assessed using in vitro assays of endothelial permeability and tumor cell trans‐endothelial migration. Thrombin‐mediated activation of PAR‐1 signalling was assessed by flow cytometry and western blotting. LMWH anticoagulant activity was assessed by calibrated automated thrombography and plasma anti‐factor Xa activity assay. Results: LMWH tinzaparin enhanced endothelial barrier function and reduced tumor cell trans‐endothelial migration (73.9±5.7% of baseline; P <.05). Tinzaparin‐mediated attenuation of thrombin‐induced permeability was not mediated through an inhibition of thrombin proteolytic activity. In addition, fractions of LMWH with diminished anticoagulant activity retained endothelial barrier protective properties and a marked synergistic effect on barrier function was observed using combinations of sub‐anticoagulant concentrations of tinzaparin with simvastatin (which exhibits endothelial barrier protective properties in vitro), with almost complete protection against agonist‐induced endothelial barrier permeability achieved (7.9±0.2% of baseline; P <.05). Conclusion: Collectively, these results suggest that LMWH supports endothelial barrier function in a manner which does not appear to be dependent on its anticoagulant activity. If replicated in vivo, these findings could represent a novel therapeutic approach to the suppression of metastasis.